2018
DOI: 10.1177/2042098618788991
|View full text |Cite
|
Sign up to set email alerts
|

Real-world incidence of patient-reported dyspnoea with ticagrelor

Abstract: Dyspnoea, a common and multifactorial symptom in patients with acute coronary syndrome, has been associated with lower quality of life and hospital readmission. Prescriber preference for antiplatelet therapy, the standard of care in this patient group, is shifting to ticagrelor due to mortality benefits demonstrated in trials compared with clopidogrel. In these trials, dyspnoea was more commonly reported in patients prescribed ticagrelor but the aetiology is still debated. An observational cohort study was con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 15 publications
1
8
1
Order By: Relevance
“…The incidence of dyspnea of any grade of severity -observed at three months-was consistent with that of the Australian study of the real-world incidence of patient-reported dyspnea with ticagrelor 22 . However, this study reported lower proportions of drug discontinuations; 1.7% versus 7.14%.…”
Section: Discussionsupporting
confidence: 82%
“…The incidence of dyspnea of any grade of severity -observed at three months-was consistent with that of the Australian study of the real-world incidence of patient-reported dyspnea with ticagrelor 22 . However, this study reported lower proportions of drug discontinuations; 1.7% versus 7.14%.…”
Section: Discussionsupporting
confidence: 82%
“…Guidelines and hospital protocols should emphasize the importance of documenting patient history, which could affect NSTEMI diagnosis, and of regularly assessing the risks and benefits of therapies to suit the patient's clinical status, which may change over time . Furthermore, guidelines and protocols should include guidance on how to manage patients with dyspnea because some physicians are concerned about dyspnea related to ticagrelor use in their patients, given that dyspnea is more frequently reported in patients with ACS prescribed ticagrelor compared with clopidogrel . The incidence of dyspnea in a real‐world setting has been shown to be greater than that reported in clinical trials and may lead to higher rates of ticagrelor discontinuation .…”
Section: Addressing the Challenges For The Treatment Of Patients Withmentioning
confidence: 99%
“…73,74 The incidence of dyspnea in a realworld setting has been shown to be greater than that reported in clinical trials and may lead to higher rates of ticagrelor discontinuation. 74 However, given that there is evidence to suggest that dyspnea can resolve during inhibitor use, only in the case of persistent ticagrelor-related dyspnea should drug discontinuation be considered. 73 There is potential for reducing the impact of geographical variation could be a reasonable approach to improve treatment outcomes for patients with NSTEMI, which could be facilitated by existing regional platforms for the management of patients with STEMI.…”
Section: Domain Of Care Quality Indicator Support From Esc Guidelinesmentioning
confidence: 99%
See 1 more Smart Citation
“…The reported incidence of ticagrelor-related dyspnoea in PHILO trial and in SOCRATES was 5.7% and 6.2%, respectively [4] . A real-world study showed that the incidence of patient-reported dyspnoea with ticagrelor was 56.0% at 3 week [5] . In recent years, some case reports and retrospective studies have shown that dyspnea associated with ticagrelor occurs not only in the early stages of drug treatment, but also may cause delayed dyspnea and even more dangerous Cheyne-Stokes (CSR) [6,7,8] .…”
Section: Introductionmentioning
confidence: 99%